Effect of Al2O3 on shear-thinning property of mould flux for high-speed thin slab continuous casting and its study on the mechanism. (2nd January 2022) - Yuan, Zhipeng; Zhu, Liguang; Xu, Ying
ABSTRACT: To solve the problems of slag entrapment risk and frequent bond alarm in the field application of mould flux for high-speed thin slab continuous casting, the idea of 'non-Newtonian fluid mould flux with shear-thinning property' is introduced. It was found that with an increase in the Al2 O3 content, the shear-thinning behaviour of the mould flux first increased and then decreased. The sample with 8.61% Al2 O3 content had the strongest shear-thinning property and the lowest fluidity index, which reached 0.75. With the addition of Al2 O3, the degree of polymerization of the mould flux molecules increased, and the relative strength of the Si–O–Al bond increased. It was found that the Al2 O3 content has a significant influence on the IV Al complexes. The XPS results showed that Q 3 (1Al) was the structural unit most easily affected by shear stress, and the higher the content of Q 3 (1Al), the stronger the shear-thinning property of the mould flux.